Judicial Responses to Pre-Trial Procedural Violations in International Criminal Proceedings - Pitcher, Kelly (International Criminal Justice Series, 2018)
This book provides an in-depth examination of the judicial response at the international criminal tribunals (ICTs) to the violation of procedural standards in the pre-trial phase of proceedings. It does so against the backdrop of the assumption that certain particularities of international criminal proceedings may warrant a different approach to the matter than at the national level. By reference to relevant human rights standards and to national criminal procedure, as well as to theoretical accounts of the judicial response to pre-trial procedural violations, this book assesses the ICTs' law and practice in this regard, thereby identifying points of concern and making suggestions for improvement. In doing so, it considers the most suitable rationale for responding to procedural violations committed in the pre-trial phase of international criminal proceedings and the merits of judicial discretion in this context, as well as the impact of certain particularities of such proceedings on the determination of how to address procedural violations. The book is intended for academics and practitioners in the field of (international) criminal law who want to gain a deeper understanding of the possible impact of pre- trial procedural violations on criminal proceedings. Kelly Pitcher is Assistant Professor of Criminal Law and Criminal Procedure at Leiden University in The Netherlands.